Factors Affecting Credit in Jordanian Commercial Banks (2010-2015) - Nadji, Ahmed Farid; Mehimid, Mounib Khalf; Daham, Daham Latif (Finance and Business Economies Review, 2019)
The study aims at identifying the factors affecting credit in Jordanian commercial banks (inflation and interest rates), independent variables, and the dependent variable bank credit. The study was conducted over the period 2010-2015. The study found that there is a statistically significant effect on inflation and interest rates on bank credit. The study also found a positive effect on inflation and a negative impact on interest rates .Therefore, the adoption of a monetary policy in the commercial banks of Jordan aims to reduce inflation rates, and adopting a banking policy at the level of Jordanian commercial banks that reduce the bank interest rates of the most important recommendations of the study.